Complementary Function of the Meniscofemoral Ligament and Lateral Meniscus Posterior Root to Stabilize the Lateral Meniscus Posterior Horn: A Biomechanical Study in a Porcine Knee Model. Issue 1 (18th January 2019) - Ohori, Tomoki; Mae, Tatsuo; Shino, Konsei; Tachibana, Yuta; Fujie, Hiromichi; Yoshikawa, Hideki; Nakata, Ken
Background: It has been demonstrated that the load distribution function of the lateral meniscus (LM) is compromised by resecting both the meniscofemoral ligament (MFL) and LM posterior root (LMPR). However, the effect of resecting these fibers on load transmission through the LM needs to be investigated. Purpose: To evaluate using a porcine knee model (1) the in situ forces of the MFL and LMPR and (2) the effect of resecting these fibers on the in situ force of the LM under a compressive load and valgus torque to the lateral knee compartment. Study Design: Controlled laboratory study. Methods: Twenty fresh-frozen porcine knees and a 6 degrees of freedom robotic system were utilized. An axial compressive load of 250 N and 5 N·m of valgus torque were applied to intact, MFL-deficient, LMPR-deficient, and MFL/LMPR-deficient knees at 30°, 60°, and 90° of flexion. The valgus angles under the applied loads were compared among the 4 states. The in situ forces of the MFL and LMPR under the applied loads were calculated under the principle of superposition. The in situ forces of the LM under the applied loads were also calculated and compared among the 4 conditions (intact, without the MFL, without LMPR, and without the MFL/LMPR). Results: The valgus angles significantly increased after resecting both the MFL and LMPR at all the flexion angles. The in situ forces of the MFL and LMPR changed reciprocally as the knee flexed. The in situ forces of the LM significantly decreased after resecting both the MFL and LMPR, although resecting only the MFL or LMPR represented no significant effect. Conclusion: The MFL and LMPR functioned complementarily as the posterior attachments of the LM against a compressive load and valgus torque to the lateral knee compartment in porcine knee joints. Clinical Relevance: If the LMPR is completely detached and needs to be repaired, the MFL should be preserved because it may provide some stability to the LM posterior horn and protect the repaired LMPR.